Positive irrational beliefs are associated with hypomanic personality - Tiba, Alexandru I.; Trip, Simona; Bora, Carmen H.; Drugas, Marius; Borz, Feliciana; Miclăuş, Daiana C.; Voss, Laura; Iova, Sorin C.; Pop, Simona (Frontiers in Psychology, 2023)
Primary irrational beliefs, such as demanding about attaining personal goals, are a common trans-diagnostic factor involved in many emotional disorders. Although Bipolar Disorder (BPD) is a severe emotional disorder, little is known about the role of primary irrational beliefs in the risk of BPD. Given that the risk for mania is related to responses to positive rather than adverse events, we developed a measure of irrational beliefs in response to cues of positive events. This is the first study that examines the relationship between positive primary irrational beliefs and the risk of BPD. 119 participants completed an online survey including measures for the risk of BPD, irrational beliefs, positive irrational beliefs, mania-related cognitions, and mood measures (depressive and manic mood). Results revealed significant associations between the risk of BPD and positive primary irrational beliefs, irrational beliefs, positive generalization, and mood. Regression analyses revealed that positive primary irrational beliefs, such as demanding to attain significant goals in response to cues for positive events, uniquely predict the risk for BPD independently of mood, mania-related cognitions and irrational beliefs. These findings encourage the treatment approaches focused on restructuring primary irrational beliefs in response to positive situations to reduce the risk of BPD.